Marker-assisted selection and DH-technology utilized to accelerate fusarium-resistant cabbage (Brassica oleracea var. capitata L.) line development - M. G. Fomicheva; G. A. Kostenko; A. S. Domblides (Овощи России, 2024)
Relevance. The use of modern biotechnological methods in breeding, namely the doubled haploid technology and marker-assisted selection, can significantly reduce the time for creating pure lines with valuable properties. Fusarium wilt is one of the economically important diseases of white cabbage. Therefore, the development of a MAS method for selecting doubled haploids resistant to fusarium wilt would allow fast selection of resistant pure lines. Moreover, the resistance testing can be done at any plant developmental stage.Materials and methods. The response of hybrids Gertsoginya F1, Poisk 2018 F1 (resistant samples, the originator – the Agrofirm “Poisk”) and Slava 1305 (susceptible sample, the originator – Federal Scientific Vegetable Center) towards Fusarium oxysporum f. sp. conglutinans infection was determined by evaluating their growth on the inoculated soil. To test the efficiency of the FocBNUf/r marker to the polymorphic region of the FocBo1 gene, the markers were tested on resistant and susceptible genotypes. Then the markers were applied to analyze 60 doubled haploids of 12 different genotypes.Results. It was demonstrated that the FocBNUf/r marker effectively differentiated resistant and susceptible samples. Doubled haploids were obtained from 12 different breeding samples for FocBNUf/r marker-based selection of fusarium wilt resistant plants. PCR testing of doubled haploids for fusarium resistance allowed us to select 6.7-100% of plants with the fusarium resistance gene in a homozygous state in 8 genotypes. 4 genotypes of doubled haploids that did not carry the resistance gene were eliminated from the breeding program.Conclusion. The FocBNUf/r marker effectively identified resistant and susceptible samples, as well as differentiates homozygous and heterozygous plants. FocBNUf/r marker was used to select resistant doubled haploids of white cabbage at the seedling stage. Thus, it was possible not only to accelerate the production of pure lines by obtaining doubled haploids, but also to accelerate the selection of valuable samples carrying the gene of resistance to fusarium, which makes it possible to avoid the labor-intensive selection of resistant lines on inoculated soil.